Expanding the phenotype of Wiedemann‐Steiner syndrome: Craniovertebral junction anomalies. Issue 12 (11th October 2020) - Giangiobbe, Sara; Caraffi, Stefano Giuseppe; Ivanovski, Ivan; Maini, Ilenia; Pollazzon, Marzia; Rosato, Simonetta; Trimarchi, Gabriele; Lauriello, Anna; Marinelli, Maria; Nicoli, Davide; Baldo, Chiara; Laurie, Steven; et al.
Abstract: Wiedemann–Steiner syndrome (WDSTS) is a rare autosomal dominant condition caused by heterozygous loss of function variants in the KMT2A (MLL ) gene, encoding a lysine N‐methyltransferase that mediates a histone methylation pattern specific for epigenetic transcriptional activation. WDSTS is characterized by a distinctive facial phenotype, hypertrichosis, short stature, developmental delay, intellectual disability, congenital malformations, and skeletal anomalies. Recently, a few patients have been reported having abnormal skeletal development of the cervical spine. Here we describe 11 such individuals, all with KMT2A de novo loss‐of‐function variants: 10 showed craniovertebral junction anomalies, while an 11th patient had a cervical abnormality in C7. By evaluating clinical and diagnostic imaging data we characterized these anomalies, which consist primarily of fused cervical vertebrae, C1 and C2 abnormalities, small foramen magnum and Chiari malformation type I. Craniovertebral anomalies in WDSTS patients have been largely disregarded so far, but the increasing number of reports suggests that they may be an intrinsic feature of this syndrome. Specific investigation strategies should be considered for early identification and prevention of craniovertebral junction complications in WDSTS patients.